TECHNOLOGICAL PRACTICE MEDIATED BY REFERENCE GROUPS: A THREE-DIMENSIONAL PERSPECTIVE - Freitas , Alan Araújo (ARACÊ, 2024)
The article aims to understand how the organizational logic of a family budget unit facilitates dialogue between the members of that unit and establishes the intermediation of information and communication between these individuals. In other words, does the family context influence technological practice and learning? Technological praxis also depends on the ability to use technology, mainly developed during schooling. Is the correlation between formal education and technological learning significant? A three-dimensional analytical model is proposed that simultaneously evaluates three independent variable factors that can directly and indirectly interfere with an individual's technological practice (dependent variable). First is the individual's access to communication technologies in their family. Secondly, the level of education achieved by the individual. Thirdly, access to communication and information technologies (ICTs) in the family of destination. Quantitative methodologies (path analysis) are used to analyze data and information on Brazil based on data from the National Household Sampling Survey (PNAD/2014).